2016
DOI: 10.7554/elife.12812
|View full text |Cite
|
Sign up to set email alerts
|

Mapping quantal touch using 7 Tesla functional magnetic resonance imaging and single-unit intraneural microstimulation

Abstract: Using ultra-high field 7 Tesla (7T) functional magnetic resonance imaging (fMRI), we map the cortical and perceptual responses elicited by intraneural microstimulation (INMS) of single mechanoreceptive afferent units in the median nerve, in humans. Activations are compared to those produced by applying vibrotactile stimulation to the unit’s receptive field, and unit-type perceptual reports are analyzed. We show that INMS and vibrotactile stimulation engage overlapping areas within the topographically appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 46 publications
6
50
0
Order By: Relevance
“…Functional MRI signal changes in S1 show a linear arrangement of individual digits ( Fig. 1) as previously described in high-resolution fMRI (Olman 2012;Panchuelo 2016;Kolasinsky 2016;Schluppeck 2017;Siero 2014;Ejaz 2015). The distance between the representations of the thumb and the little finger in S1 is 16 ± 4 mm.…”
Section: Resultssupporting
confidence: 74%
“…Functional MRI signal changes in S1 show a linear arrangement of individual digits ( Fig. 1) as previously described in high-resolution fMRI (Olman 2012;Panchuelo 2016;Kolasinsky 2016;Schluppeck 2017;Siero 2014;Ejaz 2015). The distance between the representations of the thumb and the little finger in S1 is 16 ± 4 mm.…”
Section: Resultssupporting
confidence: 74%
“…Without spatial smoothing, methods to best deal with differences in brain anatomy become vital to minimise inter‐subject spatial variability, especially for higher‐order cognitive areas for which anatomical variability is greater than for primary sensory areas (Turner & Geyer, ). Minimal anatomical variability in primary sensory cortex may, in part, explain the successes of UHF high spatial resolution studies of sensorimotor and visual cortex (Goncalves et al, ; Kemper et al, ; Poltoratski et al, ; Rua et al, ; Sanchez Panchuelo et al, ; Sanchez Panchuelo et al, ; Sanchez‐Panchuelo et al, ). Indeed, our data confirmed this observation, showing good inter‐subject correspondence of V1 (Figure b) and excellent correspondence of the anatomical and functional boundaries of V1–V3 (Figure c).…”
Section: Discussionmentioning
confidence: 99%
“…Minimal anatomical variability in primary sensory cortex may, in part, explain the successes of UHF high spatial resolution studies of sensorimotor and visual cortex (Goncalves et al, 2015;Kemper et al, 2017;Poltoratski et al, 2017;Rua et al, 2017;Sanchez Panchuelo et al, 2015;Sanchez Panchuelo et al, 2016;Sanchez-Panchuelo et al, 2012).…”
Section: Spatial Smoothingmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Kelly et al, (1997) used high density electroencephalography (EEG) over the primary somatosensory cortex (S1) and showed that stimulating single FA1 or SA1 units projecting to the hand gave characteristic peaks in power at the same frequency at which the units were stimulated. Only two studies have been performed using functional magnetic resonance imaging (fMRI) to map the spatial profile of the cortical responses to single-unit INMS (Sanchez Panchuelo et al, 2016;Trulsson et al, 2001). The earlier study, performed at 3.0 T, showed that individual type I units have corresponding neural activations in S1 and the 90 secondary somatosensory cortex (S2), and the responses were in good spatial agreement with activations from vibrotactile stimulation (Trulsson et al, 2001).…”
Section: Introductionmentioning
confidence: 99%